2013
DOI: 10.1680/geot.9.p.105
|View full text |Cite
|
Sign up to set email alerts
|

Salient factors controlling desiccation cracking of clay in laboratory experiments

Abstract: This paper elucidates some of the controlling factors governing soil desiccation. The desiccation tests were conducted on three materials -clay, potato starch and milled quartz sand -all three featuring similar fracture energy. Two controlling factors were identified in desiccation cracking, regardless of the material. The first is the tensile stress and strain energy development within the material when the material is restrained against shrinkage. The distribution of the tensile stress will depend on the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(83 citation statements)
references
References 22 publications
9
65
0
9
Order By: Relevance
“…These outcomes have been later corroborated by other researchers, such as Kodikara et al (2000) who analyzed the data of Corte and Higashi (1960) and Lau (1987), Nahlawi and Kodikara (2006), Lakshmikantha et al (2006) and Costa et al (2013). Tang et al (2008), Tang et al (2010a) and Costa et al (2013) were able to show that there was an influence of the desiccation rate in the amount of cracks produced. Rodríguez et al (2007) observed that the effects of soil thickness on the cracking water content were not noticeable for very thin soil layers.…”
Section: Accepted M Manuscriptsupporting
confidence: 57%
“…These outcomes have been later corroborated by other researchers, such as Kodikara et al (2000) who analyzed the data of Corte and Higashi (1960) and Lau (1987), Nahlawi and Kodikara (2006), Lakshmikantha et al (2006) and Costa et al (2013). Tang et al (2008), Tang et al (2010a) and Costa et al (2013) were able to show that there was an influence of the desiccation rate in the amount of cracks produced. Rodríguez et al (2007) observed that the effects of soil thickness on the cracking water content were not noticeable for very thin soil layers.…”
Section: Accepted M Manuscriptsupporting
confidence: 57%
“…Earlier studies have elucidated the mechanism of desiccation crack formation for various grain-liquid mixtures [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The mixtures typically consist of a skeleton of solid grains and pore spaces that are filled with either liquid or air bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Expansive clay soils, which are dominated by 2 : 1 clay minerals, crack during desiccation when substantial matric suction in the pore structure of the fine-grained clays develops and the tensile strength exceeds the cohesive strength of the soil matrix (Mermut et al, 1996;Nahlawi and Kodikara, 2006;Costa et al, 2013). Desiccation cracks can serve as water conduits and preferentially transport water and solutes into deep sections of the vadose zone during the generation of local runoff or occasional flooding (Bronswijk et al, 1995;Kurtzman and Scanlon, 2011;Baram et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%